ISOLATION AND IDENTIFICATION OF BACTERIA IN THE SALIVA OF A RETICULATED PYTHON ON THE ISLAND OF BALI - Shofi, Muhammad Gus; Widyastuti, Sri Kayati; Mahatmi, Hapsari (Buletin Veteriner Udayana, 2022)
The problem of wildlife is increasing every year, ranging from health to the environment and one of them is snakes. The more disturbed the habitat of snakes, the issue of snake bites become an increasing problem. One example is the reticulated python located in Bali, not only humans but other animals can also be bitten. In the snake's oral cavity, there are bacteria that can infect the bitten victim. This study aims to isolate and identify bacteria in the oral cavity of local Balinese reticulated pythons that live in nature. This research was conducted with a descriptive observational design. Samples were taken directly from the snake's oral cavity using a sterile cotton swab and inserted into the Stuart media so that it was stored in a clean cooler box. This study used 8 saliva samples of local Balinese reticulated pythons that live in nature, which were cultured using transport media Stuart Agar , Blood Agar culture media , MacConkey , Eosin Methylene Blue Agar (EMBA) and Salmonella Shigella Agar (SSA). bacterial identification media Indol, Methyl red, Voges-Proskauer, indole motility sulfide, simmons citrate (IMViC) and TSIA test, sugar fermentation test (glucose, lactose, sucrose, maltose), and Gram staining test C r y s t al violet (Gram positive), Safranin (Gram negative), other ingredients such as 70% alcohol, aquadest. Identification of samples in the laboratory of the Healthy Animal Clinic in Malang City. The results of this study found that 8 samples of saliva of local Balinese reticulated python snakes identified 1 sample (12, 5%) found the presence of Enterobacter sp. bacteria, 2 samples (25%) found Serratia sp. , Klebsiella sp. 1 sample (12.5%), Salmonella sp. in 2 samples (25%), E. coli in 1 sample (12.5%) and Proteus sp. in 1 sample (12.5%). The need for further research on the finding of Salmonella sp. in 25% of saliva samples of reticulated pythons, and also further research on the discovery of Serratia sp. in 25% of snake saliva samples.